A vertical and radial consolidation analysis incorporating drain degradation based on the spectral method. (January 2021) - Xu, Bin-Hua; Indraratna, Buddhima; Trung Nguyen, Thanh; Walker, Rohan
Abstract: The use of prefabricated vertical drains (PVDs) to improve soft soil has received much attention in the recent past, however, there is still a lack of rigorous analytical solutions that can incorporate the time- and depth-dependent behaviour of drains into the consolidation of multi-layered soil. This study thus presents a novel approach where the spectral method is used to capture the degradation in discharge capacity of drains over time and depth, while the average consolidation of different soil layers with regard to vertical and radial drainage is computed. In this approach, the excess pore water pressure profile across different soil layers is described as a single expression using matrix operations. This proposed method is then verified with laboratory and field investigations where the degradation of PVDs is captured and compared with other solutions. The results show that this method can predict the soil behaviour with greater accuracy and flexibility whereas there is a significant deviation in the predicted consolidation when the degradation of drains is not considered properly. A parametric investigation is also carried out using the proposed solution to further highlight its ability to evaluate the effect that drain degradation can have on the consolidation of multi-layered soil.